“Analisis Efektivitas Implementasi ERP sebagai Sistem InformAkuntansi dalam Penyajian Laporan Keuangan pada Perusahaan Sektor Retail di Bursa Efek Indonesia - Rio Manuel Matthew; Jose Adrian Simbolon; Ulul Azmi Fadhilah; Jumiadi AW (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the effectiveness of Enterprise Resource Planning (ERP) implementation as an accounting information system in the presentation of financial statements within retail sector companies listed on the Indonesia Stock Exchange. The research employed a descriptive qualitative approach using secondary data obtained from annual reports, financial statements, and academic literature related to ERP implementation. The findings reveal that the majority of public companies in Indonesia adopt SAP ERP platforms due to their reliability and compliance with international accounting standards. The adoption of ERP has occurred in three waves: pioneering companies in the early 2000s, massive expansion between 2010 and 2019, and an accelerated migration toward cloud-based systems during the 2020–2025 period. ERP implementation has been proven to enhance the accuracy, transparency, and timeliness of financial reporting while strengthening corporate accountability to investors and regulators. However, the study also identifies several challenges, including high investment costs complex integration with legacy systems, user resistance, and data security issues. Therefore, the success of ERP implementation is determined not only by technological sophistication but also by organizational readiness, managerial support, and human resource competence in managing digital transformation.